Cervical Cerclage: Prolonging Gestational Period for Successful Pregnancy Outcome - Akhter, Afroza; Habib, A H M Ahsan; Md Al Momen, Shahjad Hossain; Nath, Sudipto Deb (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Cervical Cerclage may be an effective treatment option in true cervical insufficiency. Cervical function plays a crucial role to protect growing fetus in utero in maintaining successful pregnancy. As the gestational weeks progress, the cervix undergoes dynamic changes, including softening and shortening, to accommodate fetal growth. Objective: The objective of this study is to evaluate the effectiveness and outcome of cervical cerclage placement as a preventive measure against recurrent pregnancy loss and preterm delivery and its complications, to analyze pregnancy outcomes among participants who received cervical cerclage and to investigate the relationship between cervical cerclage and pregnancy outcome based on gestational age. Method and Materials: The study was conducted over three years at CMH, Jashore and Ibn Sina Hospital Jashore, utilizing a retrospective and longitudinal interventional approach. Ethical approval was obtained before commencing the study, which involved 92 cases undergoing mid-trimester cervical cerclage. Cervical length measurements, cervical cerclage using the McDonald technique, and subsequent medical management were performed with outcome analyzed using descriptive statistics and odds ratio. Data were analyzed retrospectively through SPSS data analysis tool. Result: 45.65% of patients experienced term deliveries, while 33.70% had preterm deliveries, with 20.65% facing abortions. Distinct inclusion criteria unveiled diverse outcomes, such as recurrent pregnancy loss cases showing 40.82% preterm and 38.78% term deliveries. Odds ratios highlighted cervical length's significance, with a 0.25 ratio indicating reduced preterm risk. Interestingly, 61.69% of preterm births occurred between 34 and 36 weeks. Maternal outcomes indicated low incidence rates of hemorrhage (4.8%), infections (1.1%) and cervix laceration (2.4%). Conclusion: The study underscores cervical cerclage's potential in enhancing full-term pregnancies, particularly for patients with cervical incompetence. While highlighting its success, the study also acknowledges associated risks and complications. J Bangladesh Coll Phys Surg 2024; 42: 57-62